Copywriting for Teenagers’ Personal Branding on Social Media - Linda Handayani Sukaemi; Isam Samsul Muharam; Hanipah Fahirah Kamilah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
This article discusses the results of community service regarding the use of copywriting for personal branding. Participants in this training were 67% youth and 33% early adults. The activity was carried out online through Zoom meetings allowing participants from various regions in Indonesia to participate. Copywriting in personal branding can be done by conveying (a) reasons for staying in content, (b) interesting stories, (c) arguments, (d) invitations to follow the values being campaigned for. Based on the results of an assessment of the content uploaded by the participants, personal branding training is an interesting event for teenagers and the early adult generation. Copywriting material for personal branding can be practiced by participants in doing personal proof on social media Instagram. After completing copywriting training for personal branding, participants may find it easy to direct their content in conveying the messages or values they want to spread to the public.